Spontaneous and experimental poisoning by fruits of Eugenia uvalha Cambess. (Myrtaceae) in sheep Intoxicação espontânea e experimental por frutos de Eugenia uvalha Cambess. (Myrtaceae) em ovinos - Emmerich T.* (2014)
We describe the epidemiological, clinical signs and lesions of a disease of sheep characterized by apathy, sialorrhoea, teeth grinding, circling, blindness, incoordination, seizures and opisthotonos usually followed by death. The disease occurred in February and March 2009 of 2013, in the West highlands and mountanous regions of Santa Catarina State and was associated with the falling fruits of "uvaieira" (Eugenia uvalha Cambess). In farms where outbreaks occurred had loads of fruit fallen to the ground and the sheep ate them hungrily. Those who survived remained with intermittent seizures. No gross or histological changes were observed. However, the whole fruits or their fragments mixed in the content of the pre-stomachs and bowels were found. The disease was reproduced providing the uvaia ripe fruits to three sheep, in daily doses of 45,45 g/kg, 68,18 g/kg and 82,35 g/kg each, for until six days. The main way to diagnose the uvaia poisoning is the observation of the clinical and epidemiological data, associated with the presence of fruits and seeds in the gastrointestinal tract.